Research on the Coupling Coordination between New Urbanization and Land Green Use Efficiency in the Southwest China Urban Agglomeration - Li, Nanjie; Zhang, Yuhong (International Journal of Natural Resources and Environmental Studies, 2026)
Exploring the complex and dynamic relationship between new urbanization (NUR) and land green use efficiency (LGUE) contributes to optimizing the allocation of land resources and facilitating the process of NUR. This paper employed the linear weighted method to evaluate the NUR of urban agglomerations in Southwest China and utilized the Super-SBM model to calculate the LGUE. Utilizing the coupling coordination degree (CCD) model, the NUR, LGUE and spatial alterations of 33 cities in the urban agglomeration from 2008 to 2021 were analysed, and three key findings were obtained. (1) The NUR process in the study area is sluggish, and the NUR level is significantly lower than the LGUE level. (2) There are substantial spatial disparities in NUR and LGUE in the study area. The values of NUR and LGUE in provincial capital cities are relatively high. (3) The CCD of NUR and LGUE in the study area have slowly increased. The number of people engaged in scientific research and technical services and fiscal revenue are the key factors impacting the CCD. This work can serve as a reference for promoting the coordinated development of NUR and LGUE and coordinating the economic and social development and protection of the ecological environment.